Analysis of Patient Characteristics, Financing of Actions and Diagnosis of Disease in BPJS Patients - Syagran, Evy; Setianto, Budhi; Adriansyah, Agus Aan; Setiyowati, Eppy; Sa'adah, Nikmatus (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Background: Dental and oral health services are a form of professional service that is an integral part of health services for the community, families or individuals3. Implementation of a dental specialist clinic at the 2nd health facility is a referral from the health facility 1 All financing is borne by BPJS with INA CBGS financing. Purpose: This study aims to determine patient characteristics and disease diagnosis of BPJS patients in specialist dental clinic in Islamic Hospital Surabaya. Methods: This study used a qualitative research method with a descriptive analytic study. From the BPJS TXT data for January - December 2019, there were 7153 patient visits at the dental specialist clinic of the Islamic Hospital in Surabaya, the TXT data is data issued by the BPJS as a result of purification of billing file data recognized by the BPJS. Results: Based on the results of the study, it was found that most of the patients were male, with the largest age ranges being <25 years and> 50 years. The implementation of the tariff difference between INA CBGS and the fare difference of the Islamic Hospital in Surabaya is - 128,091,924 with an average of - 17,907 / patient. Of the total TXT, the largest financing of the INA CBGS tariff is the doctor service rate with a percentage of 54.90%. Conclusion: the implementation of BPJS examination of specialist dental polyclinic at RS Islam Surabaya did not give the maximum benefit.